Upaya Meningkatkan Kesadaran Masyarakat Mengenai Pentingnya Menjaga Kesehatan di Musim Pancaroba - Sumayadi, Ahmad; Permana, Deni (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
The aim of this service activity is to increase public awareness regarding the importance of maintaining health in the transition season. The implementation of this service activity is divided into several activities to improve the quality of community and family health in the transition season. The stages used in this service activity are divided into three stages, namely: social reflection, activity planning, and activity implementation. The service team carries out activities in Trimurjo Village, Trimurjo District, Central Lampung Regency. The results achieved from this service activity are that public awareness regarding the importance of maintaining health in the transition season has begun to appear, marked by residents cleaning the gutters in front of their respective homes. It is hoped that in the future such activities will be carried out routinely for the sake of collective health.